The preliminary study of the factors influencing the financial management among University Malaysia Kelantan students - Noor Hazwani Che Amad; Noor Kamilah Manap; Noor Liana Ahmad Zamri; Noor Shasha Amira Mohd Zawawi (2023)
The knowledge of financial management practices needs to be inculcated earlier among students. According Dewi (2017), " The lack of knowledge regarding financial literacy serves as a detriment to millennials, clearly causing other disruptions in their lives such as stress". This shows that good financial management practices are important for students and should not be underestimated. As a result of neglect, financial management will cause students to run into financial difficulties and become debt-ridden. Therefore, with the current, increasingly challenging economic situation, students need to manage their finances properly.